2014
DOI: 10.2478/pjen-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Potential of an Insect Growth Regulator in the Management of the Rice Moth Corcyra Cephalonica Stainton, 1866 (Lepidoptera: Pyralidae)

Abstract: The present investigation reveals the influence of methoprene, an IGR, on the ontogeny, growth duration and adult longevity of the rice moth Corcyra cephalonica. Twenty-five larvae of different instars (1st, 2nd, 3rd and 4th) of C. cephalonica were exposed to the juvenile hormone analogue methoprene in order to evaluate its potential effect on larval mortality, pupation, pupal mortality, adult emergence, growth duration and adult longevity. These different instars larvae were treated with 2, 4, 8 and 12 ppm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(42 reference statements)
3
10
0
Order By: Relevance
“…In larvicidal activity of methoprene against P. argyrostoma, in the current study, was in corroboration with some reported results of methoprene larvicidal activity against some insects, such as the mosquito Culex molestus (Farghal and Temerak, 1981), the common house mosquito Culex pipiens (Gelbic et al, 2002), the Asian tiger mosquito Aedes albopictus (Khan et al, 2016), the black cutworm Agrotis ipsilon (Khatter, 2014) and C. cephalonica (Tripathi and Tiwari, 2006). Also, the present result of methoprene pupicidal activity against P. argyrostoma agreed with those reported pupicidal activity of methoprene against some insects, such as the yellow fever mosquito Aedes aegypti (Braga et al, 2005) and C. cephalonica (Tripathi and Tiwari, 2006). In addition, exposure of 3 rd instar larvae of the flesh fly Sarcophaga ruficornis to different concentrations of Barium carbonate resulted in larval and pupal mortalities (Singh et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In larvicidal activity of methoprene against P. argyrostoma, in the current study, was in corroboration with some reported results of methoprene larvicidal activity against some insects, such as the mosquito Culex molestus (Farghal and Temerak, 1981), the common house mosquito Culex pipiens (Gelbic et al, 2002), the Asian tiger mosquito Aedes albopictus (Khan et al, 2016), the black cutworm Agrotis ipsilon (Khatter, 2014) and C. cephalonica (Tripathi and Tiwari, 2006). Also, the present result of methoprene pupicidal activity against P. argyrostoma agreed with those reported pupicidal activity of methoprene against some insects, such as the yellow fever mosquito Aedes aegypti (Braga et al, 2005) and C. cephalonica (Tripathi and Tiwari, 2006). In addition, exposure of 3 rd instar larvae of the flesh fly Sarcophaga ruficornis to different concentrations of Barium carbonate resulted in larval and pupal mortalities (Singh et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The deformed adult flies were observed with a poor ability to fly. The present result agreed, also, with the reported anti-morphogenic activity of Methoprene against some of other insects, such as Sitotroga cerealella (Stockel and Edwards, 1981), T. confusum (Smet et al, 1989) and the rice moth Corcyra cephalonica (Tripathi and Tiwari, 2006). For interpretation of the anti-morphogenic action of Methoprene on the adult flies of P. argyrostoma, as appeared in adult deformities in the present study, this juvenoid might exert an adverse action on the hormonal balance during the adult differentiation, in particular the disturbance of ecdysteroid titre which led to changes in lysosomal enzyme activity causing overt morphological abnormalities (Josephrajkumar et al, 1999).…”
Section: Morphogenic Disorders Of Adultssupporting
confidence: 92%
See 2 more Smart Citations
“…Aedes albopictus (Khan et al, 2016), Agrotis ipsilon (Khatter, 2014) and C. cephalonica (Tripathi and Tiwari, 2006). Also, the current result of methoprene lethality against P. argyrostoma agreed with the pupicidal activity of methoprene against some insects, such as Aedes aegypti (Braga et al, 2005) and C.…”
Section: Reduced Survival Of P Argyrostoma By Methoprenementioning
confidence: 58%